Health and Emergency Department Transfers for Ontario Long-Term Care Home Residents Living with Schizophrenia - Tiukuvaara, Samuel (Université d'Ottawa | University of Ottawa, 2025)
Objective. Describe long-term care (LTC) residents living with and without schizophrenia and analyze the association of schizophrenia with emergency department (ED) transfers. Design. Cross-sectional study and cohort study. Settings and Participants. Individuals admitted to Ontario LTC between 2012 and 2023. Methods. Health administrative data were retrieved. Descriptive statistics were calculated for measures of health status and need upon admission. Negative binomial regression was used to analyze ED transfer rate overall and by ambulatory care sensitive conditions in the year following admission. Results: Residents living with schizophrenia were younger and had fewer comorbidities, more stable health, lower mortality risk, more intact functioning, and similar aggressive behaviour frequency. They received less nursing and personal care. Schizophrenia was not associated with ED transfers. Conclusion and Implications. Residents living with schizophrenia require less support for general health. LTC is supporting residents living with schizophrenia but access to mental health care may be improved.
Keywords: Schizophrenia; Long-Term Care; Health Services Needs and Demand; Emergency Department